Collagen Vascular Disease Sebagai Faktor Risiko Terjadinya Mata Kering - Eka Purwanti, Mutya (CV RIFAINSTITUT, 2022)
Dry eye is one of the eye diseases that is the most common reason a person visits an ophthalmologist. Globally, the prevalence of dry eye with or without symptoms ranges from 5-50%. Dry eye is more common in women than men and increases with age. Dry eye is a disease that has many similarities to autoimmune diseases. One of the autoimmune diseases that can be a high risk factor for dry eyes is collagen vascular disease. The mechanism of dry eye in patients with collagen vascular disease is thought to occur due to the role of muscarinic acetylcholine receptor type 3 autoantigens and B cells as APCs that produce autoantibodies. This autoimmune process causes a loss of homeostasis due to the presence of inflammatory mediators that damage the lacrimal functional unit. Dry eyes that occur due to collagen vascular disease are characterized by symptoms of irritation and discomfort in the eyes. Currently, knowledge about the pathogenesis and treatment is still growing.